1979
DOI: 10.1002/cne.901870405
|View full text |Cite
|
Sign up to set email alerts
|

Regional topography within noradrenergic locus coeruleus as revealed by retrograde transport of horseradish peroxidase

Abstract: A hitherto unsuspected degree of regional topographic organization in the noradrenergic nucleus, locus coeruleus, was revealed by the use of retrograde transport of horseradish peroxidase (HRP) from terminal areas receiving noradrenergic innervation. HRP was injected into hippocampus, hypothalamus, thalamus, caudate-putamen, septum, amygdala-piriform cortex, cerebellum and cortex. Successful transport was obtained from all areas, including the caudate-putamen and cerebral cortex. The pattern of HRP positive ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
114
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(128 citation statements)
references
References 63 publications
13
114
1
Order By: Relevance
“…Noradrenergic fibers were described as highly ramified and localized in a sunburst orientation within the center of each barrel. Such organization is supported by other studies, which have shown selective connectivity between the rodent locus coeruleus (LC) and its efferent target sites (Mason and Fibiger, 1979;Cedarbaum and Saper, 1981;Waterhouse et al, 1983;Loughlin et al, 1986aLoughlin et al, , 1986bMorrison and Foote, 1986;Simpson et al, 1997). In general, these findings contradict other early investigations, which emphasized the diffuse projection pattern and global actions of the LC/norepinephrine (NE) system (Anden et al, 1966;Ungerstedt, 1971;Pickel et al, 1974;Nakamura and Iwama, 1975;AstonJones andBloom, 1981a, 1981b;Aston-Jones et al, 1986).…”
mentioning
confidence: 60%
“…Noradrenergic fibers were described as highly ramified and localized in a sunburst orientation within the center of each barrel. Such organization is supported by other studies, which have shown selective connectivity between the rodent locus coeruleus (LC) and its efferent target sites (Mason and Fibiger, 1979;Cedarbaum and Saper, 1981;Waterhouse et al, 1983;Loughlin et al, 1986aLoughlin et al, , 1986bMorrison and Foote, 1986;Simpson et al, 1997). In general, these findings contradict other early investigations, which emphasized the diffuse projection pattern and global actions of the LC/norepinephrine (NE) system (Anden et al, 1966;Ungerstedt, 1971;Pickel et al, 1974;Nakamura and Iwama, 1975;AstonJones andBloom, 1981a, 1981b;Aston-Jones et al, 1986).…”
mentioning
confidence: 60%
“…In comparable architecture of noradrenergic, dopaminergic and serotonergic systems [117,118], somata of histaminergic neurons are restricted to discrete cell clusters in the hypothalamic TMN, and send their axons to innervate nearly the entire CNS [7,8]. Cathecolaminergic and serotonergic nuclei are comprised of distinct compartments with respect to projection fields, as distinct sets of axons innervating separate brain regions originate from separate subgroups of noradrenergic (A1-A7), dopaminergic (A8-A17) and serotonergic (B1-B9) neurons [117,118].…”
Section: Heterogeneity Of Histaminergic Neuronsmentioning
confidence: 99%
“…But another possibility is that the NE axons that innervate the hypocretin neurons arise not primarily from the LC but from other NE neurons in the hindbrain, perhaps from A1 or A2, or other axons could arise from adrenergic neurons in C1 that project to the LH (Mason and Fibiger, 1979;). These cells have a different function from the LC neurons and may relate more to control of vegetative and homeostatic processes, potentially linking the enteroceptive cells of the gut with the LH.…”
Section: Functional Importance Of Ne Inhibition Of the Hypocretin Aromentioning
confidence: 99%